Design and Build a Web-Based Community Complaint Service Application System (Case Study: Sumber Mulyo Rejo Binjai East Village) - Shafira, Daniella; Rio Septian Hardinata; Hardiansyah Putra (Cattleya Darmaya Fortuna, 2026)
The rapid development of information technology provides opportunities for governments to improve the quality of public services, particularly in managing community complaints. At the village administrative level, complaint submission is often still conducted through conventional methods, which can lead to delays in handling reports, difficulties in data recording, and a lack of transparency regarding the status of submitted complaints. Therefore, a system is required to facilitate the community in submitting complaints in an easy and integrated manner. This study aims to design and develop a web-based community complaint service application for the Sumber Mulyo Rejo Village, Binjai Timur. The research method used includes observation, interviews, and literature studies to collect the necessary data for system development. The system development process consists of requirements analysis, system design, implementation, and system testing using the Black Box Testing method. The developed system allows the community to submit complaint reports, monitor the status of their reports, and access information related to submitted complaints. Meanwhile, administrators can manage complaint reports, report categories, and user data through the provided administrative panel. The results of this study indicate that the developed application system can improve the efficiency of managing community complaints and support transparency as well as easier access to public services for both the community and village administration.